Makna Oko Mama dalam Masyarakat Desa Sono Kecamatan Amanatun Utara Kabupaten Timor Tengah Selatan - Fransiska A. Lopo; Clotilde Seran; Antonius Bere; Yohanis K. Tampani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
The title of this study is the meaning of Oko Mama in the Sono Village Community, North Amanatun District, Sout Centeral Timor Regency. The purpose of this study is to find out and analyze the meaning of Oko Mama in the Sono Village Community. The theory used ini this research is using qualitative research method in analyzing data obtained in the field. In determining the informants who were interviewed, three people were used, consisting of the head of Sono Village, Traditional Elders and the Community. The results of this study indicate that the meaning of Oko Mama in the Sono Village Community, Oko Mama is a tradition inherited from ancestors that must be preserved and applied in everyday life. And in any activity, the community uses Oko Mama as the main media to open the activity. Based on the results of the study above, the author explains several things as follows: Through research, it is hoped that the people of Sono Village will love local culture more because culture has the identity of a region. And it is hoped that the community can provide knowledge for the next generation about the importance of preserving the Oko Mama culture.